APLIKASI SPEKTROSKOPI FOTOAKUSTIK LASER CO2 UNTUK PENDETEKSIAN GAS ETILEN (C2H4) PADA TANAH PADA MUSIM HUJAN - , BERGITTA DWI ANNAWATI, Dr. Mitrayana, S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research has been conducted application of CO2 laser photoacoustic spectroscopy to detect ethylene gas (C2H4) in the land in rainy season base on location and depth variation of sampel utilized photoacoustic spectrometer extracavity configuration with the source of CO2 Laser. The lowest detection limit value was yield (416 Â± 104) ppt. Ethylene concentration resulted in the land base on depth variation when rainy season was (0.18 Â± 0.04) ppm for depth 0 cm (land surface), (0.17 Â± 0.04) ppm for depth 15 cm from surface and (0.15 Â± 0.03) ppm for depth 30 cm from surface. Base on sample place variation had value (0,19 Â± 0,04) ppm, (0,18 Â± 0,04) ppm and (0,15 Â± 0,03) ppm sequencely for north, middle of place and south from UGM biologyâs forestry area thatâs located on western of Biology and Physics buildings in Science Faculty of Gajah Mada University. Ethylene consentration in the land when rainy season are not influenced by location and depth factor significantly.